Sociodemographic factors predictors of attitudes towards induced abortion (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
Around 73 million induced abortions take place worldwide each year, and 61% of all unintended pregnancies end in induced abortion.The objective of this study was to determine socio-demographic factors that predict attitudes toward induced abortion in a sample of the adult population. A quantitative cross-sectional descriptive study was carried out in Barquisimeto, Lara state, Venezuela, between June 2024 and August 2025. A survey was conducted among 244 people over 18 years of age, which included a scale of attitudes towards induced abortion (SATIA) and a set of socio-demographic factors. Descriptive and inferential statistics were used, including Cronbach's alpha, Kaiser-Meyer-Olkin measure, Bartlett's sphericity, and multivariate linear regression. The SATIA had acceptable reliability and sampling adequacy. The predictors of attitudes toward induced abortion were: age (B: 0,297; p < 0,001) and religion (B: 2,335; p = 0,004) in the Pro-life subscale; age (B: -0,308; p < 0,001), educational level (B: 0,877; p = 0,006), and religion (B: -1,465; p = 0,033) in the Pro-choice subscale; and age (B: -0,137; p < 0,001), employment (-0,924; p = 0,008), educational level (B: 0,379; p = 0,018), and female sex (B: 0,733; p = 0,038) in the Reproductive Rights subscale. The study concluded that age, religion, employment, female gender, and educational level could be predictors of attitudes toward induced abortion.
Keywords: attitudes toward abortion; induced abortion; sociodemographic factors